Cultivation of Saxaul Seedlings Using Water-Efficient Technologies to Improve Environmental Conditions and Prevent Sand Movement and Pasture Degradation - Ōktam Toshbotirovich Khakimov; Gulniso Abzal qizi Isaeva (American Journal of Biology and Natural Sciences, 2026)
The deterioration of atmospheric air quality, the frequent exceedance of dust particle norms, and the acceleration of rangeland degradation processes necessitate urgent measures to address these challenges. The increasing frequency of sandstorms and their unhindered dispersion into the atmosphere and across rangelands significantly impact the ecological situation. This situation requires scientists to develop measures to both improve the ecosystem and prevent rangeland degradation. This article focuses on nature conservation and ecosystem improvement, discussing the research conducted by scientists at the Navoi Branch of the Academy of Sciences of the Republic of Uzbekistan. This research is aimed at establishing nurseries for the propagation of Saxaul (Haloxylon) to increase greenery in the country and consistently implement the "Yashil Makon" (Green Space) nationwide project, initiated by the President of the Republic of Uzbekistan.